The outcome of surgical treatment in patients with obstructive colorectal cancer - Abdullah Kısaoğlu (Dicle Medical Journal, 2013)
orectal cancer obstructions are responsible for about 85% of colonic emergencies. The aim of this study was to investigate the results of urgent surgical intervention that applied in acute colonic obstructions related to cancer. Methods: In this study, 86 cases presenting with acute colonic obstruction who were operated with the diagnosis of colonic tumor between January 2010 and December 2010 were assessed retrospectively. Age, gender, symptoms on presentation, presence of concomitant disease, surgical methods applied, complication and mortality rates were recorded.Results: Fifty of the cases were male, 36 were female. The mean age was 63.6 years. Twenty cases had undergone emergency colonoscopic examination at diagnosis and an obstructive lesion had been observed. The surgical operations performed were right hemicolectomy in 18, sigmoid resection in 34, left hemicolectomy in 10, abdomino-perineal resection in 2, subtotal colectomy in 4, transverse colectomy in two. Primary anastomosis was performed in thirty-four cases. Mortality was observed in 12 cases. Conclusions: In selected cases of left colon cancers with obstruction, resection and primary anastomosis is generally possible. Those over 70, presence of co-morbidities, albumin level under 3 g/dl, ASA score 3 and higher, blood loss of more than 500 ml, and preoperative blood transfusion were related to the high postoperative morbidity.Key words: Colorectal cancer, obstruction, surgical treatment, outcome.